2022
DOI: 10.3389/fphys.2022.835173
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Serial Remote Ischemic Conditioning on Dynamic Cerebral Autoregulation and Brain Injury Related Biomarkers

Abstract: ObjectiveRecent studies have demonstrated the positive roles of remote ischemic conditioning (RIC) in patients with cerebrovascular diseases; however, the mechanisms remain unclear. This study aimed to explore the effect of serial RIC on dynamic cerebral autoregulation (dCA) and serum biomarkers associated with brain injury, both of which are related to the prognosis of cerebrovascular disease.MethodsThis was a self-controlled interventional study in healthy adults. The RIC was conducted twice a day for 7 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…As discussed above, this phenomenon may be attributed to the beneficial effect of RIC on cerebral autoregulation, collateral circulation, and cerebral reservoir. 24,30,32 In this study, we further found that previous hypertension history might be associated with poor efficacy of RIC. We speculate that this may be related to pathological vascular remodeling induced by hypertension.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…As discussed above, this phenomenon may be attributed to the beneficial effect of RIC on cerebral autoregulation, collateral circulation, and cerebral reservoir. 24,30,32 In this study, we further found that previous hypertension history might be associated with poor efficacy of RIC. We speculate that this may be related to pathological vascular remodeling induced by hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…As discussed above, this phenomenon may be attributed to the beneficial effect of RIC on cerebral autoregulation, collateral circulation, and cerebral reservoir. 24 , 30 , 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies suggesting that RIC applications improve microcirculation in various organs under normal and pathological conditions [57][58][59]. Although it is technically difficult to assess the effect of RIC on brain microcirculation, there is evidence that multiple RIC applications improve cerebral blood flow [60] and enhance dynamic cerebral autoregulation in healthy individuals [61], which requires further study of its effects on brain vasculature and endothelial remodeling. Nevertheless, it is already evident that RIC in pre-and postconditioning modes is protective against brain cerebrovascular cognitive dysfunction [62].…”
Section: Ric and Neuroimmunohumoral Pathwaymentioning
confidence: 99%
“…7 Previous studies have reported that RIC stimulates endogenous protective mechanisms and has a protective role particularly in brain tissue. [8][9][10] In an experimental ischemia-reperfusion model, RIC has been shown to reduce cerebral ischemia-reperfusion injury, inflammatory substances, brain edema, and neuronal apoptosis. 11,12 Thus, RIC might be beneficial for patients who have undergone EVT treatment because cerebral recanalization after ischemia is similar to ischemia-reperfusion models.…”
Section: Introductionmentioning
confidence: 99%